Organic-Inorganic Hybrid Planarization and Water Vapor Barrier Coatings on Cellulose Nanofibrils Substrates - Karasu, Feyza; Müller, Luca; Ridaoui, Hassan; Ibn ElHaj, Mohammed; Flodberg, Göran; Aulin, Christian; Axrup, Lars; Leterrier, Yves (Frontiers in Chemistry, 2018)
Diffusion barrier coatings were developed to suppress the high sensitivity to moisture of enzymatically pre-treated and carboxymethylated cellulose nanofibrils (CNF) substrates. The coatings were based on UV curable organic/inorganic hybrids with epoxy and tetraethylorthosilicate (TEOS) precursors and additional vapor formed SiNx layers. Pure epoxy enabled a two-fold decrease of the water vapor transmission rate (WVTR) of CNF and improved its transparency, however it did not properly wet to the CNF surfaces and the interfacial adhesion was low. In contrast hybrid epoxy-silica coatings led to high adhesion levels owing to the formation of covalent interactions through condensation reactions with the OH-terminated CNF surface. The barrier and optical performance of hybrid coated CNF foils was similar to that of CNF coated with pure epoxy. In addition, the hybrid coatings provided an excellent planarization effect, with roughness close to 1 nm, one to two orders of magnitude lower than that of the CNF substrates. The WVTR and oxygen transmission rate values of the hybrid coated CNF were in the range 5-10 g/m2/day (at 38°C and 50% RH) and 3-6 cm3/m2/day/bar (at 23°C and 70% RH), respectively, which matches food and pharmaceutical packaging requirements. The permeability to water vapor of the hybrid coatings was moreover found to be much lower for thinner coatings due to further UV-induced silanol condensation and faster evaporation of byproducts. The addition of a single 150 nm thick SiNx layer on the hybrid coated CNF improved its barrier performance by more than 450 times, with WVTR below the 0.02 g/m2/day detection limit.